2017
DOI: 10.1590/1980-5497201700050012
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade e anos de vida perdidos por violências interpessoais e autoprovocadas no Brasil e Estados: análise das estimativas do Estudo Carga Global de Doença, 1990 e 2015

Abstract: The study shows the importance of external causes among young people and men as a cause of premature death and disabilities, which is a priority problem in the country. The Global Burden of Disease study may support public policies for violence prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1
56

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 40 publications
6
32
1
56
Order By: Relevance
“…Brazilian laws confer the authority to declare violent or suspicious death onto the IFM, which is similar to the United Kingdom and the United States . The fact that violence was the most frequent cause of death among the unidentified bodies may also reflect the increased violence observed in Brazil, where 12% of deaths between 2012 and 2014 were from violent causes . Specifically, the state of Minas Gerais, where the present study was conducted, showed an increase of 47% in homicide rates between 1990 and 2015 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Brazilian laws confer the authority to declare violent or suspicious death onto the IFM, which is similar to the United Kingdom and the United States . The fact that violence was the most frequent cause of death among the unidentified bodies may also reflect the increased violence observed in Brazil, where 12% of deaths between 2012 and 2014 were from violent causes . Specifically, the state of Minas Gerais, where the present study was conducted, showed an increase of 47% in homicide rates between 1990 and 2015 .…”
Section: Discussionmentioning
confidence: 75%
“…8 The fact that violence was the most frequent cause of death among the unidentified bodies may also reflect the increased violence observed in Brazil, where 12% of deaths between 2012 and 2014 were from violent causes. [21][22][23][24][25] Specifically, the state of Minas Gerais, where the present study was conducted, showed an increase of 47% in homicide rates between 1990 and 2015. 23 The results showed that the most used TA B L E 2 Frequency distribution of the type of traumatic orofacial injury in the unidentified and unclaimed bodies (n = 530)…”
Section: Discussionmentioning
confidence: 99%
“…Também implica a superação dos enfoques setoriais e desarticulados de grande parte das políticas sociais e de combate à violência no país. Em confluência com a desigual estrutura social e econômica do país está a ausência de esforços políticos na concretização de políticas públicas voltadas à garantia do direito à vida, revelando uma conjuntura de omissão na qual o jovem é submetido a situações violentas (22) .…”
Section: Discussionunclassified
“…A ausência de esforços políticos na concretização de políticas públicas voltadas à garantia do direito à vida revela uma conjuntura de omissão. Em confluência com esses fatores está a desigual estrutura social e econômica do País, na qual a população mais desfavorecida é vítima preferencial da violência (22) .…”
Section: Discussionunclassified
“…Our findings show that numerous positive results have been achieved at the national and international level through actions directed at organizing the sector to provide healthcare for victims of violence, human resource development and capacity-building, and research development, demonstrating that it is possible to prevent and reduce violence that kills and injures [35][36][37][38] . Although many of these actions have not stemmed strictly from the health sector, they have an important impact on the area.…”
Section: Final Considerationsmentioning
confidence: 99%